Eleven years' experience with retinopathy of prematurity: visual results and contribution of cryoablation. Issue 3 (March 1991) - Nissenkorn, I; Ben Sira, I; Kremer, I; Gaton, D D; Krikler, R; Wielunsky, E; Merlob, P
Abstract : We report our 11 years' experience of cryotherapy for retinopathy of prematurity (ROP). Charts of 624 infants weighing under 1250 g who were admitted to our Neonatal Intensive Care Unit during 1977-87 were reviewed. Three hundred and eighty nine babies survived, and the total ROP prevalence was 57.5%. Cryotherapy was applied to 35%. Only one case (0.25%) of blindness was detected, and four babies (1%) had a final visual acuity of less than 20/200 in one eye. The complication rate following cryoablation was very low.